Identification of Research Trends in Islamic Financial Product Innovation - Judijanto, Loso; Sudarmanto, Eko; Harsono, Iwan; Afandy, Chairil; Lucky, Muhammad (West Science Interdisciplinary Studies, 2024)
This bibliometric analysis delves into the burgeoning discourse surrounding sustainable entrepreneurship's role in addressing challenges within the circular economy framework. By synthesizing a vast array of scholarly literature spanning from 2006 to 2024, the study provides comprehensive insights into the intersection of these two pivotal areas. Through quantitative techniques such as co-citation analysis and keyword co-occurrence analysis, the analysis uncovers prominent themes, research clusters, and intellectual structures within the field. The results reveal a robust body of research exploring various dimensions of sustainable entrepreneurship and the circular economy, ranging from theoretical underpinnings to practical implications. Furthermore, the study identifies influential works and emerging trends, offering valuable guidance for future research directions. This research not only enriches our understanding of how sustainable entrepreneurship can contribute to a circular economy but also holds significant implications for academia, industry, and policymaking by informing strategic decision-making and inspiring innovative practices aimed at fostering sustainability and resilience in a rapidly changing world.